Skin Temperature in Master Long-Distance Runners—Results From a Field Study at the 2018 World Master Athletics Championships - Ganse, Bergita; Degens, Hans (Frontiers in Sports and Active Living, 2020)
Older people and athletes show impairments in thermoregulation, but this has not yet been studied during a running competition. The aim of the study was to assess 1) whether there are age-related differences in skin temperature during the last stage of a race in well-trained master athletes and 2) to what extent such differences are related to running speed and sex. To investigate this, we used thermography to measure maximum skin temperatures of the head, legs and hands of participants of the 2018 World Master Athletics (WMA) Championships when they were approximately 9,600 m into a 10,000-m road race. Of the 813 runners, 404 were analysed (142 women, 262 men) including athletes of age groups 35 to 85. All ≥70-year-old athletes completed the race; all 16 non-finishers were younger. The hand temperature was lower than that of the head and legs (p<0.001). Stepwise regression revealed that head (R2adj=0.143; p<0.001) and hand temperature decreased with increasing speed (R2adj=0.092; p<0.001). Sex was the most important determinant of leg skin temperature (R2adj=0.054; p<0.001), men having higher leg temperatures than women, with a small negative contribution of speed (R2adj increased to 0.069). In conclusion, higher running speed is associated with lower skin temperatures, and leg skin temperature is lower in women than men. The absence of an age effect on skin temperature suggests that there is no impairment in heat dissipation differences in well-trained older athletes.